2020
DOI: 10.31234/osf.io/5tjaf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Your Health vs. My Liberty: Philosophical beliefs dominated reflection and identifiable victim effects when predicting public health recommendation compliance during the COVID-19 pandemic

Abstract: Philosophers and scientists have emphasized how our responses to global crises are often alarmingly ineffective. For example, people often prioritize a few nearby victims over many victims abroad. We wanted to understand individual differences in responses to public health crises during the COVID19 pandemic. Two experiments investigated how compliance with public health recommendations depended on messaging, cognitive style, and prior philosophical beliefs (Total N = 998). One of the two experiments found that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Thus, moral convictions about the importance of individual freedom can also be relevant in this context. In line with this hypothesis, Byrd and Bialek (2020) found that the more participants valued liberty over equality, the less likely they were to comply with official regulations. Thus, we hypothesized that (H3) individuals who build their moral convictions on liberty considerations would be less likely to endorse health recommendations.…”
Section: Moral Values and Dispositionsmentioning
confidence: 59%
“…Thus, moral convictions about the importance of individual freedom can also be relevant in this context. In line with this hypothesis, Byrd and Bialek (2020) found that the more participants valued liberty over equality, the less likely they were to comply with official regulations. Thus, we hypothesized that (H3) individuals who build their moral convictions on liberty considerations would be less likely to endorse health recommendations.…”
Section: Moral Values and Dispositionsmentioning
confidence: 59%
“…Social identities are integral components of the ITT (Morrison et al, 2009). In the US, differing social identities, such as race, ethnicity, political identity, and gender, were associated with varying perceptions of COVID-19 health threats (Byrd & Bialek, 2020;DeSalvo et al, 2022;Pew Research Center, 2020;Rothgerber et al, 2020), possibly due to low versus high power group membership. High power groups are motivated to defend their privileged status quo, whereas low power groups are less committed to the norms in place (Kamans et al, 2010;Kteily et al, 2013).…”
Section: Covid-19-related Threat Perceptions and Social Identitymentioning
confidence: 99%
“…Within the first month of the pandemic, the Pew Research Center (2020) found that more Democrats than Republicans were concerned with realistic threats. Further, conservative identity was negatively associated with social distancing (Rothgerber et al, 2020), mask wearing, and hand washing (Byrd & Bialek, 2020). Instead, Republicans were threatened by procedures and mandates involving the dismantling of American traditions (i.e., symbolic threats).…”
Section: Covid-19-related Threat Perceptions and Social Identitymentioning
confidence: 99%
See 1 more Smart Citation